(untitled) (Ibrahim Cardiac Medical Journal, 2012)
Background & objective: Stroke is the third major cause of morbidity and mortality in the world immediately following ischemic heart disease and malignancy. Diabetes mellitus increases risk of ischemic stroke and mortality and morbidity after stroke. This cross sectional study was carried out to observe clinical profile of ischemic stroke in Type 2 diabetic patient. Materials & Methods: This cross-sectional study was done in the Department of Neurology, Bangladesh Institute of Research and Rehabilitation for Diabetes, Endocrine, and Metabolic Disorders (BIRDEM) Hospital, from April to September 2010. A total of 50 ischemic stroke patients with type-2 diabetes were consecutively recruited. Ischemic stroke was confirmed by clinical examination and CT imaging. Data were analysed using SPSS (Statistical Package for Social Sciences) and were presented as mean ± SD and frequencies with corresponding percentages as appropriate. Results: Of the 50 ischemic patients, over one-third (36%) was in their 6th decades of life. A male preponderance (1.5:1) in the series. Most of the patients presented with weakness on either side of the body (90%) followed by difficulties in speech (80%), altered consciousness (24%) and facial weakness (4%). On examination 76% were conscious and oriented. Other examination findings were hemiparesis (60%), hemiplegia (30%), dysarthria (72%) and dysphagia (4%). The major co-morbid condition was hypertension (86%) with mean systolic and diastolic blood pressures being 153 ± 5 and 97 ± 4 mmHg respectively. On admission 94% had normal pulse and 40% abnormal fundoscopic examination in the form of hypertensive and diabetic retinopathy. Only 2% had carotid bruit. Conclusion: Elderly males are more prone to develop ischemic stroke. Hemiparesis and dysarthria are the major clinical presentation and hypertension might be an important risk factor for ischemic stroke. Further study is recommended to conclusively comment on the clinical features of diabetic ischemic stroke patients and also to compare the clinical profile between diabetic stroke patients. Ibrahim Cardiac Med J 2012; 2(2): 14-18